NiS gradient distribution on arrayed porous carbonized grapefruit peel for water splitting. Issue 8 (30th January 2023) - Zhang, Xiaoyun; Zhu, Shifan; Song, Lili; Xu, Yixue; Wang, Yuqiao
Abstract : The Ni 2+ combined with natural S to modulate NiS and S concentration gradient distribution and form NiS on APC, enhancing the electrocatalytic performance for water splitting. Abstract : Metal-based catalysts on biomass carbon substrates can combine their respective advantages of composition and structure to improve the catalytic performance. Herein, NiS supported on grapefruit peel derived array porous carbon (APC) was obtained via a carbonization process without emission of toxic gases. The natural S source from grapefruit peel reacted with nickel salt solution. The gradient distribution of NiS and S on the APC substrates can be altered by the concentration of impregnating salt solution. Theoretical calculations showed that the S gradient distribution on APC could tune the electronic structure and optimize the adsorption energies of the intermediates. NiS was firmly anchored on the porous carbon framework, resulting in enhanced high intrinsic activity, exposure of more active sites, and accelerated mass transfer. The active mass density was proposed to build a relationship between active metal content and electrolyte diffusion capacity for the evaluation of catalytic properties.